دراسة الظروف الجيوهندسية لسد بيت سوراك في محافظة اللاذقية (Latakia University Journal -Basic Sciences Series, 2018)
يتناول هذا البحث إيضاح الخصائص الليتولوجية والجيولوجية الهندسية لمحور السد ونفوذية التوضعات على المحور وبحيرة التخزين وتم تحديد الوحدات الجيولوجية الموجودة والمتباينة بخصائها الجيوهندسية حيث صنفت هذه الوحدات أيضا تبعا لنفوذيتها في نطاقين أساسيين: نطاق نفوذ في الأعلى تبلغ سماكته في مركز بحيرة السد / 6m / وتزداد هذه السماكة لتصل في منطقة الأكتاف إلى حوالي / 16m / ويقع تحته نطاق كيتم غضاري سيلتي. كما بينت نتائج دراسة الصفات الفيزيائية والليتولوجية للصخور المشكلة لأكتاف السد أنها ذات نفوذية يجب أخذها بعين الاعتبار في أثناء التصميم. The research shows the lithological and geo – engineering properties of the dam axis and the penetration along this axis, and the dam lake. The research also localizes the geological units, which differ in its geo – engineering properties. These units were classified according to there penetration to two strips: -  penetrating strip at the dam top . The thickness of this strip at the centre of the dam lake is 6m, but this thickness increases until it reaches 16m at the dam shoulders. -  Under this strip there is unpenetrating Celtic limestone strip. Moreover, as a result of the study of the physical and litho logical properties of the rocks forming the dam shoulders, it is clear that we can’t ignore the penetration of these rocks when designing the dam.